O guardião da Constituição: o Supremo Tribunal Federal como poder autônomo no julgamento da Lei da Ficha Limpa - Rossi, Luís Antônio (2016)
This thesis aims at analyzing the position of the Supreme Court when examining the constitutionality of the Clean Record Law subsuming the decision on the debate brought by jurists Hans Kelsen and Carl Schmitt on a country s Judicial Review. Through analysis and reflection on who should be the "guardian of the Constitution", this investigation seeks to demonstrate that the Brazilian constitutional system has adopted Kelsen s positivism. However, the amplitude of the 1988 Constitution, the process of Law constitutionalization , the ideology of fundamental rights and the idleness of both the Executive (lack of an efficient public administration) and the Legislative (legislative inertia) transformed Brazilian Supreme Court into a hybrid court: sometimes as a true Constitution Court in the formalistic conception of Kelsen (judgment of the Amnesty Law, for example) or as a true Reich President or a Moderator Power in Schmitt s conception. By addressing and analyzing the judgement of the Clean Record Law this thesis claims that the Brazilian legal system has been going through a crisis caused by too much constitutionalization of law and has therefore caused the Supreme Court to change into an autonomous power: the Legal Reich